Guía de buenas prácticas de producción en bovinos de leche. - Morales López, Alisson Michelle (2023)
This project is made to guide small and medium producers, who do not have sufficient knowledge for increasing the herd and getting better income, the aim this study is to develop a guide about good manufacturing practices in dairy cows, it presents Basic Principles and useful concepts for understanding the natural milk production process, they explain breeding techniques and sanitary management applied to cows in milk production, describing good milking practices. What they learn to collect milk, properly, and how to know to handle the animals, so that their investment pays off. Furthermore, here it will find quality indicators, such as milk composition, minerals and solutes, fats, among others, that not only help to know the products quality offered to their consumers, but also improve and get better benefits from itself. This is because the media and especially small producers do not count, that in order to get quality products and get better wages, they must know how to handle animals, manage food, water, manage young and above animals all health.